UNDERSTANDING HOW CONSUMER’S FNB ENGAGE WITH DIGITAL STOREFRONT - Selamat Zebua; Gloria Anathasya; Yuli Puspitasari (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
The acceleration of information technology, the internet, the internet of things (IoT) and the application of artificial intelligence have changed all the faces of the industry from the conventional way of entering the transformation phase to digitalization. An era where digital devices have facilitated the mobility of business transactions to be more effective, efficient and unlimited. Due to the advancement of digitalization, smart shopping behaviour makes it easier for urbanites to look for references for various types of needs. This study aims to determine the effect of Digital Storefront, Ease of Use and Usefulness on Repurchase Intention moderated by e-Trust and e-Satisfaction. Data were collected using an online questionnaire to accurately 348 customers who were on the island of Java and some outside Java. The research model developed was analyzed using Structural Equation Modeling - Lisrel. The empirical results in this research model show that the Digital Storefront Hypothesis on e-Satisfaction and e-Trust on Repurchase Intention has no significant effect, while the rest states that it has a significant effect. Some of the practical implications drawn in this study can be used as recommendations to e-commerce companies to help them understand the behavioural intentions of consumers' buyers. This study presents empirical evidence that supports digital storefronts as an entry point for easy access to various e-commerce media platforms. Keywords: Digital Storefronts, Usefulness, Ease of use, e-Trust, e-Satisfaction, Repurchase Intention   Akselerasi teknologi informasi, internet, internet of things (IoT) dan penerapan kecerdasan buatan telah mengubah seluruh wajah industri dari cara konvensional memasuki fase transformasi menuju digitalisasi. Era dimana perangkat digital telah memudahkan mobilitas transaksi bisnis menjadi lebih efektif, efisien dan tidak terbatas. Karena kemajuan digitalisasi, perilaku belanja yang cerdas semakin memudahkan kaum urban untuk mencari referensi berbagai jenis kebutuhan. Penelitian ini bertujuan untuk mengetahui pengaruh Digital Storefront, Ease of Use dan Usefulness terhadap Repurchase Intention yang dimoderatori oleh e-Trust dan e-Satisfaction. Pengumpulan data dilakukan dengan menggunakan kuesioner online kepada 348 pelanggan secara akurat yang berada di Pulau Jawa dan sebagian di luar Jawa. Model penelitian yang dikembangkan dianalisis menggunakan Structural Equation Modeling - Lisrel. Hasil empiris pada model penelitian ini menunjukkan bahwa Digital Storefront Hypothesis terhadap e-Satisfaction dan e-Trust terhadap Repurchase Intention tidak berpengaruh signifikan, sedangkan sisanya menyatakan berpengaruh signifikan. Beberapa implikasi praktis yang ditarik dalam penelitian ini dapat digunakan sebagai rekomendasi bagi perusahaan e-commerce untuk membantu mereka memahami niat perilaku pembeli konsumen.   Kata Kunci:  Etalase Digital, Kegunaan, Kemudahan Penggunaan, Kepercayaan Digital, Kepuasaan Digital, Niat Pembelian Kembali